Ideological group persuasion: A within-person study of how violence, interactivity, and credibility features influence online persuasion - Taylor, W.; Johnson, Genevieve; Ault, M.; Griffith, J.; Rozzell, B.; Connelly, S.; Jensen, M.; Dunbar, N.; Ness, A. (2015)
Ideological groups (both non-violent and violent) make extensive use of the Internet for recruiting and other purposes, yet little is known about the effectiveness of the influence of websites of differing ideologies on attitudes and behavior. Furthermore, although credibility and interactivity have been extensively studied in online settings, they have received scant attention with regards to ideological groups. Using a within-subjects design, this study explored how individuals’ attitudes, emotional reactions, behaviors and behavioral intentions are affected by two separate websites, with one promoting a liberal ideology and one promoting a conservative ideology. Results indicated that individuals preferred the liberal ideology, that violent websites led to higher negative affect and lowered perceptions of credibility than the non-violent websites, and that violence decreased the likelihood of taking action. Additionally, high interactivity increased the salience of the credibility manipulations with regards to their impact on the likelihood of taking action.